Optimalisasi Asesmen Autentik dalam Transformasi Kompetensi Religiusitas Siswa pada Pembelajaran PAI di Madrasah - Puspa Dwi Putri; Agnesty Widila; Muhammad Fakhri Ridhatama; Nur Hidayat; M. Hidayaturrahman (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study aims to analyze the optimization of authentic assessment in transforming students' religious competence in Islamic Education (PAI) subjects. The primary focus of the study is directed at implementing evaluation techniques that transcend cognitive boundaries toward the internalization of students' spiritual values at MTs Nur Rahma, Bengkulu City. This study employs a qualitative approach with a case study type, where data were collected through participant observation, in-depth interviews with PAI teachers, and portfolio documentation of 8th-grade students. The results indicate that the use of performance-based assessment, projects, and self-assessment instruments significantly captures the development of students' morality and ritual skills precisely. The transformation of religious competence is evident in the increased awareness of independent worship and academic integrity, which are more stable compared to conventional evaluation models. The main challenge identified is the administrative burden on teachers; however, madrasa policy support and parental involvement are key supporting factors for the success of this system. This study concludes that authentic assessment is a vital instrument in realizing holistic and contextual Islamic education within the madrasa environment.